Factors in the HIV risk environment associated with bacterial vaginosis among HIV-negative female sex workers who inject drugs in the Mexico-United States border region - Jennifer P. Jain; Claire C. Bristow; Heather A. Pines; Alicia Harvey-Vera; Gudelia Rangel; Hugo Staines; Thomas L. Patterson; Steffanie A. Strathdee (BMC, 2018)
Abstract Background Bacterial vaginosis (BV) is the most common cause of vaginitis among women worldwide and is associated with increased susceptibility to sexually transmitted infections (STIs), including HIV. We aimed to determine the impact of the HIV risk environment on BV among female sex workers who inject drugs (FSW-PWIDs) in Tijuana and Ciudad Juarez, Mexico. Methods We performed a cross-sectional analysis utilizing baseline data from a randomized controlled trial evaluating a behavioral HIV prevention intervention. Participants underwent testing for BV using the OSOM BVBlue® Rapid Test (Genzyme Diagnostics, San Diego, CA) and completed a survey eliciting information on the HIV risk environment, sexual risk behaviors, and substance use. We applied logistic regression to identify correlates of BV in the physical, social, economic, and political HIV risk environments stratified by study site (Ciudad Juarez vs. Tijuana). Results In total, 584 HIV-negative FSW-PWIDs (300 Ciudad Juarez; 284 Tijuana) were enrolled. The prevalence of BV was 39% (n = 228), which was higher in Ciudad Juarez (56.7%) compared to Tijuana (20.4%). In both cities, micro-level components of the physical HIV risk environment were associated with BV. In Ciudad Juarez, BV was associated with past experiences or threats of physical violence in response to proposed condom use (adjusted odds ratio [aOR] = 3.66, 95% confidence interval [CI]: 1.74-7.69, p = 0.001) and lifetime residence in Ciudad Juarez (aOR = 1.74, 95% CI: 1.05-2.87, p = 0.031). In Tijuana, BV was associated with the number of hours spent on the street daily in the past six months looking for, using, or dealing drugs, engaging in other income generating activities, or sleeping (aOR = 1.05, 95% CI: 1.001-1.097, p = 0.045). Conclusions Our findings suggest that FSW-PWIDs' risk of BV may be shaped by the microphysical HIV risk environment. Addressing components of the physical risk environment, including interventions to reduce gender-based violence, may alleviate the burden of BV and subsequent susceptibility to HIV/STIs among FSW-PWIDs in the Mexico/US border region. Trial registration National Institute of Health (NIH) Clinical Trials Identifier NCT00840658, and date of NIH trial registration February 7, 2009.